CHRONIC STRESS AS A MODULATOR OF THE IMMUNE SYSTEM: NEUROENDOCRINE MECHANISMS, IMMUNOLOGICAL PATHWAYS AND CLINICAL CONSEQUENCES - A LITERATURE REVIEW - Martyna Susek,; Amadeusz Furmanek,; Anna Wawrzeczko,; Maciej Jakubiec,; Mariusz Suchcicki, (International Journal of Innovative Technologies in Social Science, 2026)
Chronic stress is a significant factor influencing human immune system functioning. Prolonged activation of the hypothalamic-pituitary-adrenal (HPA) axis and the sympathetic nervous system leads to hormonal and immunological dysregulation (Glaser & Kiecolt-Glaser, 2005; Segerstrom & Miller, 2004). Consequently, immune cells become less sensitive to glucocorticoids, cytokine balance is disrupted, and the organism remains in a state of chronic low-grade inflammation. These changes increase susceptibility to infections, delay wound healing, weaken vaccine responses, and may exacerbate the course of chronic diseases, including autoimmune and inflammatory disorders (Segerstrom & Miller, 2004; Alotiby, 2024).This review presents current data from clinical and immunological studies published between 2000 and 2025. Molecular and cellular mechanisms are discussed, including HPA axis dysfunction, excessive sympathetic activity, cytokine profile alterations, and changes in innate and adaptive immunity. Attention is given to populations particularly vulnerable to chronic stress and the clinical consequences of these dysregulations (Katz et al., 2025; Chan et al., 2023; Bolton, 2024).The review also considers strategies to mitigate stress-related immune impairment, such as mindfulness and meditation, regular physical activity, cognitive-behavioral therapy, and sleep hygiene improvement (Black & Slavich, 2016; Creswell et al., 2012; Carlson et al., 2007; Nieman & Wentz, 2019). Understanding these mechanisms may support clinical practice by enabling better identification of high-risk patients and the implementation of effective interventions.